KRAB domain of ZFP568 disrupts TRIM28-mediated abnormal interactions in cancer cells. (18th May 2020) - Kumar, Janani; Kaur, Gundeep; Ren, Ren; Lu, Yue; Lin, Kevin; Li, Jia; Huang, Yun; Patel, Anamika; Barton, Michelle C; Macfarlan, Todd; Zhang, Xing; Cheng, Xiaodong
Abstract: Interactions of KRAB (Krüppel-associated box)-associated protein KAP1 [also known as TRIM28 (tripartite motif containing protein 28)] with DNA-binding KRAB zinc finger (KRAB-ZF) proteins silence many transposable elements during embryogenesis. However, in some cancers, TRIM28 is upregulated and interacts with different partners, many of which are transcription regulators such as EZH2 in MCF7 cells, to form abnormal repressive or activating complexes that lead to misregulation of genes. We ask whether a KRAB domain—the TRIM28 interaction domain present in native binding partners of TRIM28 that mediate repression of transposable elements—could be used as a tool molecule to disrupt aberrant TRIM28 complexes. Expression of KRAB domain containing fragments from a KRAB-ZF protein (ZFP568) in MCF7 cells, without the DNA-binding zinc fingers, inhibited TRIM28–EZH2 interactions and caused degradation of both TRIM28 and EZH2 proteins as well as other components of the EZH2-associated polycomb repressor 2 complex. In consequence, the product of EZH2 enzymatic activity, trimethylation of histone H3 lysine 27 level, was significantly reduced. The expression of a synthetic KRAB domain significantly inhibits the growth of breast cancer cells (MCF7) but has no effect on normal (immortalized) human mammary epithelial cells (MCF10a). Further, we found that TRIM28 is a positive regulator of TRIM24 protein levels, as observed previously in prostate cancer cells, and expression of the KRAB domain also lowered TRIM24 protein. Importantly, reduction of TRIM24 levels, by treatment with either the KRAB domain or a small-molecule degrader targeted to TRIM24, is accompanied by an elevated level of tumor suppressor p53. Taken together, this study reveals a novel mechanism for a TRIM28-associated protein stability network and establishes TRIM28 as a potential therapeutic target in cancers where TRIM28 is elevated. Finally, we discuss a potential mechanism of KRAB-ZF gene expression controlled by a regulatory feedback loop of TRIM28–KRAB.